THE GLOBAL ECONOMIC CRISIS AND ITS IMPACT ON INDONESIAâS EDUCATION - Kuncoro, Mudrajad (Journal of Indonesian Economy and Business, 2011)
This paper will examine to what extent the unprecedented global financial crisis hasÂ affected the Indonesiaâs economy. The differences between Indonesiaâs experience of theglobal financial crisis (GFC) and Asian Financial Crisis (AFC) in 1997â98 will beÂ illuminated. The governmentâs priority on the development of educationâ together withÂ achieving quality growth, reducing poverty, creating jobs, improving infrastructureâ haveÂ accelerated the economic recovery and improved key indicators in education. Despitebudgetary adjustments, the Indonesian government continues to prioritize investment inÂ education. As a result, the GFC has not affected number of students in Indonesiasignificantly. The GFC has not affected the interest of students to get higher education atÂ the Indonesiaâs universities.Â Keywords: global financial crisis, Asian financial crisis investment, economic recovery